Sistem Informasi Manajemen Presensi Berbasis SMS Gateway Dengan Bootstrap (Studi kasus : SMP Muhammadiyah 1 Kartasura) - Saputro, Nugroho Ari; , Dr. Heru Supriyono, M.Sc (2016)
SMP Muhammadiyah 1 Kartasura (The First Muhammadiyah Junior High School of Kartasura) is a private school located in Ahmad Yani Street No.160 Kartasura. The school needs as computerized system that can manage student, teacher, and employee presences with (Short Message Service) SMS Gateway, because the student presence system in this school is still manual, using paper. Thus, the presence of this system can help manage the presence and recapitulate tidily in computer system and the parents can monitor their children's presence at school through SMS. The presence management system is made using PHP and HTML programming language; then template preparation was conducted using Bootstrap, while MyQSL was used for database management. SMS Gateway was developed using Gammu as its service. This presence system with SMS Gateway was expected to help the teachers manage and recapitulate student, teacher, and employees presences. This system was equipped with SMS Gateway used to report presence when anyone asked for permission and was sick that can be done by student's parents and teachers. Then, student's parent could monitor their children's presence using SMS with specified format. The examination was carried out using black box and questionnaire distributed randomly to teachers, students, employees and parents. The examination using black box showed that the system could work and run well corresponding to the objective of system. The examination using questionnaire showed that 24.5% respondents answered very agree, 58% agree and 17% fairly agree so that overall the system developed was useful.